2014
DOI: 10.22401/jnus.17.3.07
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Spectrophotometric Determination of Tetracycline Hydrochloride Indosage forms using Sodium Nitroprusside and Hydroxylamine Hydrochlorid

Abstract: An optimized and validated spectrophotometric method has been developed for the determination of Tetracycline hydrochloride (TCH) in pharmaceutical formulations. The method is based on the reaction between TCH, sodium nitroprusside and hydroxylamine hydrochloride in alkaline medium. The product absorbed maximally at 529 nm. Beer's law is obeyed in the working concentration range of 2-60 µg mL-1 with apparent molar absorptivity of 5.049×10 3 L mol-1 cm-1 and Sandell's sensitivity of 0.0952 µg cm 2 / 0.001 absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(8 reference statements)
2
3
0
Order By: Relevance
“…It was indicated that NaOH gave maximum colour intensity in 385 nm Figure 2. The results were compatible with the previous research which indicate that the reaction can be done in a basic medium [30,31]. 3.…”
Section: Type Of Basesupporting
confidence: 93%
See 1 more Smart Citation
“…It was indicated that NaOH gave maximum colour intensity in 385 nm Figure 2. The results were compatible with the previous research which indicate that the reaction can be done in a basic medium [30,31]. 3.…”
Section: Type Of Basesupporting
confidence: 93%
“…Comparing the obtained resulted with published work [5,30,31,35]. As can be seen in Table 10, the proposed method has higher sensitive than the cited works.…”
Section: Figure 9 Standard Addition Curve To Determine Tcs Capsulementioning
confidence: 61%
“…found is 0.0125 μg/mL and the limit of quantification (LOQ) is 0.0412 μg/mL. This LOQ obtained is approximately 35 times lower than that (1.739 μg/mL) reported for the spectrophotometric method [3]. It is close (0.026 μg/mL) to that reported for HPLC [6].…”
Section: Discussionsupporting
confidence: 47%
“…A large number of analytical techniques for the determination of tetracycline and its degradation products have been reported, particularly in biological fluids and pharmaceuticals such as spectrophotometry [2] [3] which is of limited utility due to its non-specificity. More efficient separative methods, such as capillary electrophoresis [4] and high performance liquid chromatography [5] [6] using UV and fluorescence detectors require a lot of time, proven expertise and a very high operating cost.…”
Section: Introductionmentioning
confidence: 99%
“…All different concentrations SSAS of tetracycline antibiotic used in this research were prepared from dilution of the stock solution with distilled water to the desired concentration. Tetracycline concentrations were determined spectrometrically at a wavelength of λ=529 nm using a spectrophotometer according to the method described by (12) . Figure 1 shows the spectrophotometer calibration curve intended for tetracycline concentrations.…”
Section: Stock Solutionsmentioning
confidence: 99%